The impact of evidence lineups on fingerprint expert decisions. Issue 5 (12th July 2020) - Kukucka, Jeff; Dror, Itiel E.; Yu, Melissa; Hall, Lisa; Morgan, Ruth M.
Summary: Forensic examiners routinely compare a crime‐relevant mark of unknown origin against a single suspect's sample, which may create an expectation that the two will match. We tested how embedding the suspect's sample among known‐innocent fillers (i.e., an evidence lineup ) affects expert decision‐making. Experienced fingerprint examiners ( N = 43) compared crime‐relevant marks against either individual suspect fingerprints (i.e., the standard procedure) or arrays of fingerprints (i.e., evidence lineups), with a matching fingerprint either present or absent. Evidence lineups promoted conservative decision‐making, as evidenced by fewer correct IDs and a higher rate of inconclusive judgments. Though errors were rare, evidence lineups also occasionally revealed errors that would have otherwise gone undetected. Our findings thus support arguments that evidence lineups can expose fraud, identify flawed methodologies, and curb overconfidence. The potential benefits and challenges of implementing evidence lineups in forensic laboratories are discussed.